PROBLEMS IN UNDERSTANDING THE STRUCTURE OF ARABIC SENTENCES IN CLASS VII STUDENTS OF MTS AL-ITTIHADIYAH MEDAN - Sitorus, Nurul Jumadissaniyah; al Rasyid, Harun (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This article explains the problems faced by students in understanding the jumlah al-ismiyyah in class VII MTs Al-Ittihadiyah students. The method used in this research is a descriptive qualitative research method with data collection techniques using direct interviews with 32 students. The findings in this research, firstly, students have difficulty recognizing sentence forms in Arabic, secondly students tend to be able to just read Arabic text without knowing what position the words are in the sentence, thirdly students tend to have difficulty distinguishing between mubtada' and khobar in a sentence. A new discovery in this research is that there are students' misunderstandings in studying the material on the number of al-ismiyyah. Students tend to be indoctrinated that every word at the beginning of a sentence must occupy the position of mubtada' and the words after it must occupy the position of khabar.